XTREAMS TOOLKIT UI DEVELOPMENT ON MICROSOFT WPF TECHNOLOGY - Manusmare, Rutuja Pramod; Sariki, Tulasiprasad (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â This project is a software application that runs with the station controller. When an error appears at the station controller it triggers a response flow checklist (RFC). An RFC is a troubleshooting procedure that helps you fix problems in manufacturing. A RFC is a series of instructions you define to help a manufacturing technician troubleshoot an equipment-related problem while processing. Trigger is a combination of micro-conditions. When a trigger occurs XTREAMS system automatically, it retrieves the RFC associated with that trigger. Authoring is the process of creating RFCs using the XTREAMS authoring tool. One can use the XTREAMS authoring tool to create RFC flow diagrams that the XTREAMS execution tool will display as step-by-step instructions for the RFC user. During running of a tool if the equipment is not ok, there could be multiple reasons or causes (C1, C2). These causes could be isolated by running a pre-defined checklist, that is, RFC. After the RFC and the triggers than are associated are approved using the XTREAMS Authoring Application the contents are send over to the various Intel Sites which are XTREAMS enabled. The toolkit that is provided with XTREAMS product provides one a unique capability to translate the received RFC contents to geo-specific languages so that the RFCs are relevant for the users of that particular geo. The aim here is the XTREAMS toolkit UI development on Microsoft Windows Presentation Foundation Technology so as to make it even more efficient and reliable, also which will set it free for unit tests to be performed appropriately. The MVVM framework has been followed for the purpose of development.